Health of the War Worker (London : Labour Research Department)
1942-04 1942 1940s 44 pages Sanitation Under section 7 of the Factories Act, "sufficient and suitable sanitary conveniences shall be provided."* They must be kept clean and properly lighted and there must be separate accommodation for the sexes. Many works have introduced women workers without making proper provision for this. It is extremely common, too, to find the lavatories in factories in a most revolting condition, ill-lit, with a high proportion of the flushes not functioning, unsupplied with toilet paper, and obviously not having been whitewashed or painted for years. Frequently a number of the closet seats are missing and often a pan is cracked and leaking, while a handbasin, soap, and towel are not conveniently placed, as they should be, for washing after use of the lavatory. Workers should not tolerate these conditions and should see that the management and they themselves conform to the standards they require in their own homes. Cloakrooms Under Section 43 of the Factories Act, adequate and suitable accommodation for clothing not worn during working hours must be provided and maintained, and also such arrangements as are reasonably practical for drying such clothing. Lack of attention to this means that more workers catch cold and lose time from work, owing to working or travelling home in damp clothing. Here again many factories have neglected to provide properly for their "new" women workers, in spite of the fact that the Health of Munitions Workers Committee called attention to this need in the last war. There should be a separate peg or locker for each worker with a name or number on it. Hanging pegs must not be too close together, 20—24 inches apart is necessary, and space should be made for changing clothes and boots. Washing Facilities This item is of the very foremost importance. In a great many processes it is extremely hard for workers to avoid getting their skins directly contaminated with dangerous dusts, or other unhealthy substances such as oil. Factories Act, Section 42 (1) states: There shall be provided and maintained for the use of employed persons adequate *The standards are for men, 1 convenience per 25 workers; where over 100 are employed, 1 per 40 workers above 100, and 1 per 60 above 500: and for women, 1 per 25 workers. 7 21/2049